Research on the Performance Analysis of Meituan - Wang, Rongtian (Transactions on Social Science, Education and Humanities Research, 2024)
The pandemic has had a devastating impact on China’s economy. People and purchasing behavior have changed a lot since then. This brings threats and opportunities at the same time for companies, and companies need to adapt to survive and grow after the disaster. As a result, this study’s research objective is to analyze and suggest changes to an e-commerce company running in China Meituan. The research methods in this study are listed as follows: First, the data for the company performance is used, followed by the Pestle analysis and portal five forces theory To analyze future threats and market changes in China. The third is to analyze the internal factors of Meituan to find its strengths and short backs. Finally, it is by combining the information gathered to suggest Meituan. This study indicates that Meituan has done well in the past; with the opportunity provided after the pandemic and its competitive advantage, Meituan can earn a dominant place in the Chinese market.